2014
DOI: 10.1002/elps.201300471
|View full text |Cite
|
Sign up to set email alerts
|

Charge profiling and stability testing of biosimilar by capillary isoelectric focusing

Abstract: CIEF was developed for the rapid analysis of charge heterogeneity of trastuzumab biosimilar using commercially available fluorocarbon-coated capillary. The CIEF master mix was composed of 0.30% w/v methyl cellulose, 2.3 M urea, 56.8 mM l-arginine, 1.52 mM iminodiacetic acid, 4.5% v/v carrier ampholytes (broad-range pI 3-10 and narrow-range pI 8-10.5 with ratio of 3:1), and 0.45% v/v 10.0, 9.5, 7.0, 5.5, 4.1 pI markers. To get a robust method to analyze charge heterogeneity, some separation parameters, includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…cIEF method was developed for confident identification of differences in charge-related characteristics of proteins. The same year, Cao et al described a cIEF analysis of trastuzumab biosimilar in terms of charge profiling and stability testing [61]. They realized optimization on focusing time and separation temperature to get a robust method to analyze charge variants.…”
Section: Applicationsmentioning
confidence: 99%
“…cIEF method was developed for confident identification of differences in charge-related characteristics of proteins. The same year, Cao et al described a cIEF analysis of trastuzumab biosimilar in terms of charge profiling and stability testing [61]. They realized optimization on focusing time and separation temperature to get a robust method to analyze charge variants.…”
Section: Applicationsmentioning
confidence: 99%
“…Similarly, there is potential application in the comparison of innovator and biosimilar molecules to reveal differences that may be masked by the complexity of isoelectric profile of the intact molecule. 34 It remains to be seen if the ChromiCE method can be incorporated upstream of a mass spectrometry method; however, the potential wealth of information that may result is quite intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…cIEF method combines the advantage of IEF and CZE as an automatic technique with high resolution and precise calculation of pI value for each component [28,34]. Ahn et al [27] and Alejandro Cifuentes et al [28,29] reported the analysis of rhuEPO isoforms by cIEF.…”
Section: Introductionmentioning
confidence: 99%